Change in exacerbation rate of COPD patients before and after COVID-19 infection - Joon Young Choi; Kyung Joo Kim; Chin Kook Rhee (Scientific Reports)
Abstract The COVID-19 pandemic has profoundly affected global health system, significantly altering not only the acute management of viral infection, but also management strategies for chronic diseases. This study aimed to investigate the impact of COVID-19 infection on exacerbation rates and the economic burden in patients with COPD. We conducted a retrospective cohort study using data from the national insurance reimbursement data of South Korea. Eligible participants included COPD patients diagnosed with COVID-19 between January and December 2020. We analyzed exacerbation rates, healthcare utilization, and medical costs pre- and post-COVID-19 infection. In 3,445 COPD patients who were infected by COVID-19, COVID-19 infection resulted in increased annual moderate-to-severe and severe exacerbations compared to pre-COVID-19 infection (IRR = 1.062 [95%CI 1.027–1.099]; IRR = 1.315 [95%CI 1.182–1.481], respectively). Among previously non-exacerbators, 11.2% of patients transitioned to exacerbator after COVID-19 infection. Older age, comorbidities and use of triple therapy were the factors associated with transitioners. Direct medical costs escalated significantly from approximately $6810 to $11,032, reflecting the increased intensity of care after COVID-19 infection. COVID-19 infection has significantly increased rate of exacerbations in patients with COPD and imposed a heavier economic burden on healthcare system. Among non-exacerbators, substantial number of patients transitioned to exacerbators after COVID-19 infection.